Exploring students’ perceptions of the mandatory TOEFL ITP test and its relationship with academic anxiety: A study on final-year students at Hamzanwadi University - Jannatu Kholdi Al-Hafizi; Yulia Agustina; Astrid Dwimaulani; M. Adib Nazri (Journal of Classroom Action Research, 2025)
In Indonesia, many universities have implemented the TOEFL ITP test as a mandatory graduation requirement to ensure students’ English proficiency meets academic and professional standards. This study aimed to examine the relationship between students’ perceptions of the mandatory TOEFL ITP policy and their academic anxiety. Using a quantitative correlational design, data were collected from 25 final-year students of the English Education Study Program at Hamzanwadi University through an online questionnaire consisting of two parts: perceptions of the TOEFL ITP policy (8 items) and academic anxiety (10 items), both measured on a four-point Likert scale. The data were analyzed using descriptive statistics and Pearson Product-Moment Correlation. The results showed that students’ perceptions were moderate (M = 22.32, SD = 3.22), and their academic anxiety was also moderate (M = 27.64, SD = 5.45). The Pearson correlation analysis revealed no significant relationship between students’ perceptions and their academic anxiety (r = 0.023, p = 0.911, p > 0.05). This finding indicates that students’ perceptions of the TOEFL ITP policy do not have a direct effect on their academic anxiety levels, rather, anxiety is influenced by factors such as readiness, confidence, and coping strategies. Theoretically, this study provides new insights into the link between language testing policies and psychological responses, while practically, it suggests that universities should offer preparatory programs, counseling services, and institutional support to help students manage anxiety and perform better in the TOEFL ITP test. Overall, the study highlights the need to integrate assessment policies with student well-being strategies in higher education